2009
DOI: 10.1007/s10661-009-0880-2
|View full text |Cite
|
Sign up to set email alerts
|

Land-use change simulation and assessment of driving factors in the loess hilly region—a case study as Pengyang County

Abstract: The main objective of this study is to evaluate the land-use change and its relationship with its driving factors in the loess hilly region. In this study, a case study was carried out in Pengyang County. We set two land-use demand scenarios (2) forest and grassland were the land-use types with highest commission errors, which implies that conversion of both the land-use types mentioned above is the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 13 publications
0
16
1
3
Order By: Relevance
“…In the last decades, numerous studies have focused on land use status, the evolution of landscape pattern, forecasting future land use change, etc. (Zhao et al, 2012;Zhu et al, 2010;Verburg et al, 2002). In China, a number of studies have demonstrated the landscape pattern changes using LUCC data in urban areas (Zhang et al, 2014;Peng et al, 2013;Pan et al, 2012), watersheds (Wang et al, 2014), wetlands (X.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, numerous studies have focused on land use status, the evolution of landscape pattern, forecasting future land use change, etc. (Zhao et al, 2012;Zhu et al, 2010;Verburg et al, 2002). In China, a number of studies have demonstrated the landscape pattern changes using LUCC data in urban areas (Zhang et al, 2014;Peng et al, 2013;Pan et al, 2012), watersheds (Wang et al, 2014), wetlands (X.…”
Section: Introductionmentioning
confidence: 99%
“…Land use change models are usually used to illustrate land use change and its relationship with driving forces. Even so, it is complicated to assess driving forces of land use change [9]. Spatially explicit modeling of Land use changes is an important technique for describing processes of change in quantitative terms and for testing our understanding of these processes [10].…”
Section: Introductionmentioning
confidence: 99%
“…CLUE-S is an empirical analysis-based model that considers the influences of geophysical and socioeconomic driving factors on land-use category changes [41][42][43][44][45][46][47][48][49]. The main purpose of the transformation of the land-use type and the spatial allocation in the CLUE-S model was to provide a reference for predicting green manure intercropping.…”
Section: Introductionmentioning
confidence: 99%